MORTGAGING SYSTEM IN GOODS MARKET BRANCH PAWNING GRASS - Ahmad Bayhaqi; Diyah Ruri Irawati, Skom, MMSi (Jurnal Sistem Informasi, 2006)
In this writing, the author wants to create a system that has been computerized pawnthis stuff is made in lieu of systems that still use it manually cause a lot of problemsin data processing is data - the data is often lost or mixed up. Therefore, thesecomputerized systems that have very well applied to the company that servesnumerous manuscripts. Related to this writing, the author discusses the system ofmortgage products and programs using Microsoft Visual Basic 6.0